THE EFFECT OF CUSTOMER EXPERIENCE AND SERVICE QUALITY ON PURCHASE DECISION OF EVENT & WEDDING ORGANIZER SERVICES (STUDY ON EVENT & WEDDING ORGANIZER SEVEN PRODUCTION) - M. Eka Marshanda Pramestyan (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
Although marriage rates are decreasing, the wedding industry continues to grow due to the increasing use of event & wedding organizer services for practicality reasons. Intense competition demands companies to provide memorable experiences and high-quality services in order to be hired by consumers. The purpose of this study was to test and analyze the effect of customer experience and service quality on purchase decisions at event & wedding organizers. The study was conducted at Event & Wedding Organizer Seven Production. Research type is a quantitative research, data collection techniques using a Likert scale questionnaire. The sampling technique uses nonprobability sampling through convenience sampling method with a sample size of 130 respondents. The statistical analysis used in this study is multiple linear regression with the help of IBM SPSS Statistics 27 software. The results of this study indicate that customer experience has a significant influence on purchase decisions, and also service quality has a significant influence on purchase decisions.